PENGARUH POLITICAL CONNECTION DEWAN DIREKSI DAN DEWAN KOMISARIS TERHADAP RETURN ON EQUITY DAN ASSET TURNOVER PERUSAHAAN DI SEKTOR KONSTRUKSI - Patrick A Suhartono; Sany Sany Sany (Business Accounting Review, 2016)
The purpose of this study was to know whether there was significant influence of political connection of the board of directors and board of commissioners on the ROE and asset turnover. The results from this study demonstrated that the political connection of the board of directors and board of commissioners had no affect on ROE and asset turnover. Firm size has positive effect on ROE and asset turnover. The board size has a significant influence on ROE.